Teacher Performance Assessment Decision Support System Using Topsis Method - Yogi Kurnia (Institute of Computer Science, 2019)
Decision Support System is a means of assisting in making decisions accurately, and quickly. In the Decision Support System, several methods can be applied including the TOPSIS method. The TOPSIS (Technique For Order Preference by Similarity to Ideal Solution) method is a multi-criteria decision-making method or alternative choice which is the alternative that has the smallest distance from the positive ideal solution and the largest distance from the negative ideal solution from a geometric point of view using Euclidean distance. The results of the TOPSIS (Technique For Order Preference by Similarity to Ideal Solution) method based on data and criteria determined by the Deli Serdang Education Office, an assessment was made of teacher performance at SD Negeri 105336 Rantau Panjang.